SOMEA: self-organizing map based extraction algorithm for DNA motif identification with heterogeneous model - Lee, Nung Kion; Wang, Dianhui (BioMed Central Ltd, 2011)
Background: Discrimination of transcription factor binding sites (TFBS) from background sequences plays a key role in computational motif discovery. Current clustering based algorithms employ homogeneous model for problem solving, which assumes that motifs and background signals can be equivalently characterized. This assumption has some limitations because both sequence signals have distinct properties.